In Silico Approaches to the Design of NS5A Inhibitors - A. Ivanenkov, Yan; S. Veselov, Mark; A. Aladinskiy, Vladimir; G. Shakhbazyan, Artem; M. Yartseva, Sofya; G. Majouga, Alexander; V. Aladinskaya, Anastasia; S. Vantskul, Anton; V. Leonov, Sergey; V. Ivachtchenko, Alexandre; E. Koteliansky, Victor (Current Topics in Medicinal Chemistry, 2016)
In recent years, nonstructural protein 5A (NS5A) has rapidly emerged as a promising therapeutic target for Hepatitis C (HCV) virus therapy. It is involved in both viral RNA replication and virus assembly and NS5A plays a critical role in the regulation of HCV life cycle. NS5A replication complex inhibitors (NS5A RCIs) have demonstrated strong antiviral activity in vitro and in vivo. However, wild-type resistance mutations and a wide range of genotypes significantly reduce their clinical efficacy. The exact mechanism of NS5A action still remains elusive, therefore several in silico models have been constructed to gain insight into the drug binding and subsequent structural optimization to overcome resistance. This paper provides a comprehensive overview of the computational studies towards NS5A mechanism of action and the design of novel small-molecule inhibitors.
Keywords: modeling